2018
DOI: 10.1186/s12864-018-4602-4
|View full text |Cite
|
Sign up to set email alerts
|

New insight into the mechanism underlying the silk gland biological process by knocking out fibroin heavy chain in the silkworm

Abstract: BackgroundExploring whether and how mutation of silk protein contributes to subsequent re-allocation of nitrogen, and impacts on the timing of silk gland degradation, is important to understand silk gland biology. Rapid development and wide application of genome editing approach in the silkworm provide us an opportunity to address these issues.ResultsUsing CRISPR/Cas9 system, we successfully performed genome editing of Bmfib-H. The loss-of-function mutations caused naked pupa and thin cocoon mutant phenotypes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 58 publications
1
15
0
Order By: Relevance
“…Disruption of FibH expression significantly reduced silk production, and the FibH −/− animals only formed very thin cocoon shells ( Fig. 4 A ), similar to previous reports ( 32 , 33 ). In comparison, both MaSp1 +/− and MaSp1 +/+ animals spun silk and formed elliptical cocoon shells ( Fig.…”
Section: Resultssupporting
confidence: 90%
“…Disruption of FibH expression significantly reduced silk production, and the FibH −/− animals only formed very thin cocoon shells ( Fig. 4 A ), similar to previous reports ( 32 , 33 ). In comparison, both MaSp1 +/− and MaSp1 +/+ animals spun silk and formed elliptical cocoon shells ( Fig.…”
Section: Resultssupporting
confidence: 90%
“…These cellular stress responses were also observed in FibH knock-out silkworms using CRISPR/Cas9 system [47]. The loss-offunction mutation caused an accumulation of abnormal FibH protein and aroused the activation of proteasomes as well as autophagy process in the silk gland cells [47], which was consistent with our results for the autophagy assay and suggested that accumulation of secretion-deficient (abnormal or mutant) FibH protein in the silk gland cells might lead to more activation of autophagy process to promote the rapid degradation of such abnormal proteins and in cells. Thus, we suspected that the cellular stress responses might be caused by the secretion-deficient fibroin protein that is encoded by the CRISPR-activated FibH gene in BmE cells, further raising the possibility that secretion-deficient FibH was responsible for the PSG cell atrophy in fibroin-deficient B. mori mutants.…”
Section: Discussionmentioning
confidence: 65%
“…Therefore, the stressed cells initiate adaptive responses aiming at reducing damage to the cells, such as a decrease in global protein translation and an increase in proteins of the proteolytic system [38,[44][45][46]. These cellular stress responses were also observed in FibH knock-out silkworms using CRISPR/Cas9 system [47]. The loss-offunction mutation caused an accumulation of abnormal FibH protein and aroused the activation of proteasomes as well as autophagy process in the silk gland cells [47], which was consistent with our results for the autophagy assay and suggested that accumulation of secretion-deficient (abnormal or mutant) FibH protein in the silk gland cells might lead to more activation of autophagy process to promote the rapid degradation of such abnormal proteins and in cells.…”
Section: Discussionmentioning
confidence: 93%
“…Ubiquitin is a small and highly conserved polypeptide of 76 amino acids reported in different organisms that is involved in proteins degradation [ 43 ] and (in mammals) in the posttranslational modifications of plasma membrane proteins and voltage-gated sodium channels (Na v ) in a process called ubiquitylation [ 44 ]. Although the role of this protein in spider venoms is not clear (besides the role in silk glands and proteins degradation [ 43 , 45 ]), it may be involved in the Nav activation after envenomation, since P. verdolaga ubiquitin’s similarity and a conserved domain at the α-subunit C-terminal make Na v potential targets for the ubiquitins. The activation of these channels may play an important role during envenomation, facilitating the action of toxins and affecting Na v , which plays a synergic role, the later being previously reported in P. verdolaga [ 10 ].…”
Section: Discussionmentioning
confidence: 99%